1999
DOI: 10.2307/2656809
|View full text |Cite
|
Sign up to set email alerts
|

Floral plasticity in an iteroparous plant: the interactive effects of genotype, environment, and ontogeny in Campanula rapunculoides (Campanulaceae)

Abstract: Phenotypic variation in 11 floral and reproductive traits was studied in cloned plants of Campanula rapunculoides replicated in three discrete environments. Using an ANOVA approach, we determined the relative influence of genotype (G), environment (E), G × E interaction, and ontogeny (position on the raceme) on the 11 traits. Two traits, duration of flowering and pollen size, showed no significant variation. All nine remaining traits had significant genotypic variation, accounting for 21-38% of the total pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 76 publications
6
79
0
1
Order By: Relevance
“…Our observation that the production of testes was not affected by competition is similar to past studies showing that male reproductive traits, such as pollen number and size and sperm number, are less sensitive than are female traits to environmental variation (Young et al 1994, Havens et al 1995, Vogler et al 1999, Newlon et al 2003. Additionally, in hermaphroditic organisms, an emphasis on male reproduction frequently occurs in high-density and nutrient-depleted situations (Newlon et al 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Our observation that the production of testes was not affected by competition is similar to past studies showing that male reproductive traits, such as pollen number and size and sperm number, are less sensitive than are female traits to environmental variation (Young et al 1994, Havens et al 1995, Vogler et al 1999, Newlon et al 2003. Additionally, in hermaphroditic organisms, an emphasis on male reproduction frequently occurs in high-density and nutrient-depleted situations (Newlon et al 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Physiological mechanisms include changes in selfincompatibility (SI) that allow for delayed selfing. SI systems generally prevent self-fertilization; however, a temporal breakdown in expression during anthesis, or transient SI, can be a mechanism (4) Geraniales (1) Myrtales(2) Crossosomatales Picramniales Sapindales (2) Brassicales(1) Santalales Berberidopsidales Caryophyllales(1) Cornales(1) Ericales(5) Garryales Gentianales (7) Solanales (2) Boraginales (1) Lamiales (7) Asterales ( Goodwillie et al, 2004) and Campanula rapunculoides (Campanulaceae, Vogler et al, 1999). Intriguingly, transient SI is accompanied by reduced herkogamy in Leptosiphon and progressive stigma curvature in Campanula, both of which promote late deposition of self-pollen as flowers become self-compatible (Stephenson et al, 2000;Goodwillie unpub.…”
Section: Mechanisms Of Delayed Selfingmentioning
confidence: 99%
“…Mazer and Schick 1991;Boose 1997;Vogler et al 1999) extremely little is known about G × E interactions in pollen competitive ability. Vogler et al (1999) concluded that pollen traits are well buffered against environmental variation in Campanula rapunculoides. In their study, the only pollen trait in which significant G × E interactions were found was pollen viability.…”
Section: Discussionmentioning
confidence: 99%